Identifying 4a’s Component (Attraction, Accessibility Amenity, And Ancillary) In Sade Tourism Village - Devi Kartika Sari Utomo; Meriyati Huka Gusadi; Utari Azalika Rahmi; Givano Ramadhan; Wiwik Dwi Pratiwi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Sade Tourism Village plays an important role as a cultural tourism destination that maintains the cultural heritage of the Sasak tribe through daily life practices and the architectural characteristics of its buildings. As a tourism destination, tourism components such as attractions, accessibility, amenities and ancillaries in the Sade Tourism Village are crucial aspects that require careful planning and management to ensure the continued existence of the destination. This research aims to identify and analyze the existing conditions of the Sade Tourism Village, so that recommendations for developing 4A components can be prepared that can support the sustainability of tourism activities in the Sade Tourism Village. This research was conducted in the Sade Tourism Village which is located in Rembitan Village, Pujut District, Central Lombok Regency. Data collection methods include field observations, interviews with relevant stakeholders and literature studies to understand destination dynamics, map existing conditions, identify problems and formulate strategic recommendations. The data was analyzed using a qualitative descriptive analysis approach to describe and explain the information collected and formulate recommendations that are appropriate to the context and conditions of the Sade Tourism Village. The research results describe the existing conditions of attractions, accessibility, amenities and ancillaries in Sade Tourism Village, as well as the development needs required. The resulting recommendations include maintaining and improving the main attractions of the village; improving infrastructure and tourism support facilities in villages; as well as increasing active promotion and marketing.